Development of Amperometric Laccase Biosensor through Immobilizing Enzyme in Magnesium-Containing Mesoporous Silica Sieve (Mg-MCM-41)/Polyvinyl Alcohol Matrix. (12th January 2014) - Dai, Z.; Guo, M. Q.; Wang, X. J.; Wang, H. F.; Chen, W. Y.
Abstract : Magnesium-containing mesoporous silica sieve (Mg-MCM-41) provided a suitable immobilization of biomolecule matrix due to its uniform pore structure, high surface areas, fast electron-transfer rate, and good biocompatibility. Based on this, an amperometric biosensor was developed by entrapping laccase into the Mg-MCM-41/PVA composite matrix. Laccase from Trametes versicolor was assembled on a composite film of Mg-MCM-41/PVA modified Au electrode and the electrode was investigated by cyclic voltammetry, impedance spectroscopy, and chronoamperometry. The results indicated that the Mg-MCM-41/PVA/Lac modified electrode exhibited excellent catalytic activity towards catechol at room temperature in pH 4.8 acetate buffer solution. The optimum experimental conditions of biosensor for the detection of catechol were studied in detail. Under the optimal conditions, the linear range was from 0.94 to 10.23 μ M with the sensitivity of 16.9227 A/M, the detection limit of 0.00531 μ M, and the response time of less than 14 s. The Michaelis-Menten constant (K M app ) was estimated by Lineweaver-Burk equation and the K M app value was about 1.01 μ M. In addition, the biosensor exhibited high reproducibility and long-time stability. This work demonstrated that Mg-MCM-41/PVA composite provides a suitable support for laccase immobilization and construction of biosensor.